Relationship Between Soil Structure and Botanical Composition of The Flat Pastures in Costal Region of Samsun Province - Mut, Hanife; Ayan, Ilknur; Acar, Zeki; Basaran, Ugur; Tongel, ozgur; Asci, ozlem (Asian Journal of Chemistry, 2010)
This study was conducted in 14 different flat pastures representing Samsun Coastal region. The relationships among the soil structure with plant covered area, botanical composition and distribution of the plants according to their families were inspected in these pastures. Average altitudes of these pastures were about 4 m. Observations and measurements were done between 26th April and 17th May 2005 and transect method was used for measurements. Considering each pasture zone, soil samples were analyzed to determine the general soil characters. Silty, sandy clay and different soil textures with different compositions of these soil characters were determined in the pastures. Generally, organic matter contents were high in the clay soil pastures, moderate in the silty soil pasture and moderate and low in the sandy soil pastures. Nitrogen contents of the pasture soils were between 0.007 and 0.043 %, pH values varied from 7.2 to 8.7. Phosphorous contents of the soil samples were between 1.846 and 23.080 ppm; lime content were between 0.20 and 12.82 %; salt contents were 146.2-974.4 μ mhos/cm; C/N ratio was 12.14 and 48.4. Plant covered areas of the pastures changed between 35.62 and 84.80 %. Generally clay soil pastures had higher plant covered area values than other pastures. Considering the plant families, it is observed that silty soil pastures had more legumes and sandy soil pastures had the plants belonging to the other families. However, any other relationship could not be determined between soil structure and the grass family-plants.